2004
DOI: 10.1302/0301-620x.86b6.13400
|View full text |Cite
|
Sign up to set email alerts
|

The functional outcome of severe, open tibial fractures managed with early fixation and flap coverage

Abstract: We studied the outcome and functional status of 33 patients with 34 severe open tibial fractures (Gustilo grade IIIb and IIIc). The treatment regime consisted of radical debridement, immediate bony stabilisation and early soft-tissue cover using a muscle flap (free or rotational). The review included standardised assessments of health-related quality of life (SF-36 and Euroqol) and measurement of the following parameters: gait, the use of walking aids, limb-length discrepancy, knee and ankle joint function, mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(86 citation statements)
references
References 41 publications
5
79
0
2
Order By: Relevance
“…Orthopedic training may be compromised because of the reduced fracture incidence. Patients might benefit from the competence gathered at specialized centers with intensive multidisciplinary involvement to cover all the diagnostic and treatment options required (Gopal et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Orthopedic training may be compromised because of the reduced fracture incidence. Patients might benefit from the competence gathered at specialized centers with intensive multidisciplinary involvement to cover all the diagnostic and treatment options required (Gopal et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Gopal et al studied the outcome of patients with open tibial fractures (Gustilo grade IIIb or IIIc) and found that only 40% of them returned to work [23].…”
Section: Discussionmentioning
confidence: 99%
“…The initial evaluation of a patient with orthopaedic trauma must include a detailed assessment of the soft tissue envelope. The timing and method of fracture fixation are directly influenced by the degree of trauma to the overlying soft tissues and have been shown to have a direct effect on postoperative function [5,8,13,14,17].…”
Section: Historymentioning
confidence: 99%